Respect for Patient Confidentiality Must Not Be Dependent Upon a Fee: The Case of Adolescents’ Access to Contraceptives in Ontario - Brisson, Julien (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
In Ontario, adolescents can be confidentially prescribed contraceptives. However, some adolescents must pay pharmacies to have their confidentiality respected when it comes to contraceptives; if their parents’ private insurance plan covers them, the adolescent has to pay out of pocket to be given contraceptive in a confidential manner. It is unethical to make anyone pay to have their confidentiality respected, particularly for a vulnerable population like adolescents who tend to be economically disadvantaged.